Perception of the use of chlorine dioxide and degree of knowledge about COVID-19 in Medical students from a Peruvian university - Copaja Corzo, Cesar (2021)
Objective: To determine the perception of the use of chlorine dioxide (CDS) and the degree of knowledge about COVID-19 in medical students of a Peruvian university. Material and methods: Cross-sectional observational study. A virtual survey of 158 medical students from the Jorge Basadre Grohmann National University was conducted from 15 to 18 August 2020. The instrument used was divided into three sections: socio-demographic characteristics, level of knowledge about COVID-19 and attitudes towards the use of CDS. Bivariate analysis was performed using Fisher's exact test. Results: Of the 158 medical students surveyed, 53 % were women, the average age was 21 (RIQ: 19-23) year-old. 22 % consider that if a doctor or health care staff recommends the use of chlorine dioxide, it is because it has some utility in treating COVID-19, and 39 % have low knowledge about the disease. There is a difference between the perception regarding the use of chlorine dioxide and the level of knowledge about COVID-19 (p<0.05). Conclusion: Almost a quarter of students consider the use of chlorine dioxide to treat COVID-19 useful if recommended by a doctor or if conventional medical therapy does not work. This may be due to a low level of knowledge about the disease.